Alloy Engineering of 2D Van der Waals Chromium Mixed Trihalides as Ferromagnetic Semiconductors. Issue 2 (1st December 2021) - Chen, Ying; Wang, Guangzhao; Yuan, Hongkuan; Chen, Hong
Abstract : The electronic and magnetic properties of 2D‐layered chromium mixed trihalide CrXY2 (XY = IBr, ICl, BrCl) and W‐alloyed chromium mixed trihalide CrWX2 Y4 monolayers are investigated by employing the combination of density functional theory and Monte Carlo (MC) simulation. The dynamical stability, the possibility of formation, and the structural stability of these pristine and alloyed chromium mixed trihalide monolayers are verified by the phonon spectra, the negative formation enthalpies, and the negative cohesive energies, respectively. All of them are intrinsic ferromagnetic (FM) semiconductors with the easy axis along z while along x for CrICl2 monolayer. The Curie temperatures ( T C ) of pristine chromium mixed trihalide monolayers are estimated to be 40–70 K by the MC simulations. FM ordering of alloy compound CrWX2 Y4 monolayers is largely enhanced up to T C ∼ 170 K. Thus, alloy engineering can be a route to the room temperature FM semiconductors. Abstract : Ferromagnetic ordering of two‐dimensional layered chromium mixed trihalides is largely enhanced by isovalent alloying. Typically, for the alloy compound CrWI2 Br4 monolayer it is enhanced up to the Curie temperature of 187 K in contrast to 65 K of CrIBr2 monolayer.